2010
DOI: 10.1177/0363546509356979
|View full text |Cite
|
Sign up to set email alerts
|

A Profile of Injuries in Athletes Seeking Treatment during a Triathlon Race Series

Abstract: Shorter distance triathlons have lower injury rates and relatively minor injuries, but medical teams and race organizers should be prepared for serious injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 28 publications
7
53
1
2
Order By: Relevance
“…Data from elite half Ironman events have shown similar injury rates (10%), whereas the Hawaii Ironman Triathlon has a lower injury rate (17%) than our data in this nonelite race. 5 There were 61 total presentations and 85 total injuries in the Ironman distance event, whereas there were 36 presentations and 46 injuries in the half Ironman event. The most common primary diagnosis at the Ironman distance was dehydration (50.8%) followed by muscle cramps (36.1%).…”
Section: Injury Profiles and Rate Of Injuriesmentioning
confidence: 98%
“…Data from elite half Ironman events have shown similar injury rates (10%), whereas the Hawaii Ironman Triathlon has a lower injury rate (17%) than our data in this nonelite race. 5 There were 61 total presentations and 85 total injuries in the Ironman distance event, whereas there were 36 presentations and 46 injuries in the half Ironman event. The most common primary diagnosis at the Ironman distance was dehydration (50.8%) followed by muscle cramps (36.1%).…”
Section: Injury Profiles and Rate Of Injuriesmentioning
confidence: 98%
“…Multiple abrasions or lacerations and contusions or haematomas were considered as 1, leading to an underestimation of the total number of abrasions and contusions and therefore leading to an underestimation of the injury rate. The comparison of injury rates and incidences with other road cycling-related sports such as triathlon,18 19 off-road cycling 13 20–23 or off-road motorcycle racing24 is limited because of the difference in injury definition and methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, athletes who had higher skill were at greater risk to get injured [6]. Most of the research studies found that lower limb injury reported increasing every year [7][8][9][10][11][12]. The Scandinavian's study stated that sports injuries conquer 19% of all kinds of injuries, and knee and ankle injuries had the larger number of injury cases [12].…”
Section: Fig1 Percentage Distribution Of Nature Of Injuriesmentioning
confidence: 99%
“…The study also found that high incidence of injury occurrence in lower limbs (59.9%) compared with the upper extremity region (20.8%). Injuries to the lower limb accounted for 59.5% of all reported injuries with the record of 188 cases [7]. Anterior cruciate ligament injuries were reported as the severe knee injuries among all knee injuries [12].…”
Section: Fig1 Percentage Distribution Of Nature Of Injuriesmentioning
confidence: 99%